2019
DOI: 10.1038/s41598-019-48958-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the MADS-box genes highly expressed in the laticifer cells of Hevea brasiliensis

Abstract: MADS-box transcription factors possess many functions in plant reproduction and development. However, few MADS-box genes related to secondary metabolites regulation have been identified. In H evea brasiliensis , natural rubber is a representative cis -polyisoprenoids in secondary metabolism which occurs in the rubber laticifer cells, the molecular regulation basis of natural rubber biosynthesis is not clear. Here, a total of 24 MADS-box genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…A recent study also indicated that MADS-box genes were involved in the regulation of natural rubber (NR) biosynthesis. Rubber tree HblMADS24 binds to the promoter of HbFPS1 , a key enzyme-encoding gene involved in NR biosynthesis, and transcriptionally activates the HbFPS1 promoter, suggesting that HblMADS24 is a transcriptional activator of HbFPS1 [ 26 ]. HbMADS4 binds with the promoter of HbSRPP , and transient overexpression of HbMADS4 in tobacco was shown to repress the activity of the HbSRPP promoter significantly [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also indicated that MADS-box genes were involved in the regulation of natural rubber (NR) biosynthesis. Rubber tree HblMADS24 binds to the promoter of HbFPS1 , a key enzyme-encoding gene involved in NR biosynthesis, and transcriptionally activates the HbFPS1 promoter, suggesting that HblMADS24 is a transcriptional activator of HbFPS1 [ 26 ]. HbMADS4 binds with the promoter of HbSRPP , and transient overexpression of HbMADS4 in tobacco was shown to repress the activity of the HbSRPP promoter significantly [ 27 ].…”
Section: Introductionmentioning
confidence: 99%